The Use of Slang Among Students of the Faculty of Economics, State University of Medan and Its Influence on the Ability to Speak Good and Correct Indonesian - Lestari, Bunga Indah; Nugraha, Fathan Arya; Lingga, Frans Fanca Putra; Aruan, Mario; Ananda, Riski (EDUCTUM: Journal Research, 2024)
This study aims to determine the effect of the use of slang on the ability to speak good and correct Indonesian among students of the Faculty of Economics, State University of Medan. This study uses a descriptive quantitative method by distributing a questionnaire in the form of a linear scale to 60 randomly selected students. The results of the study indicate that there is a slight tendency that the more often students use slang, their ability to speak good and correct Indonesian decreases slightly, but the effect is not significant. This study suggests that students should be more aware of the importance of using good and correct Indonesian, especially in academic environments.